Development of cofee trees grafted on Apoatã IAC 2258 cultivated in nematode-free field - Pereira Dias, Fábio; Guimarães Mendes, Antônio Nazareno; Mendonça de Carvalho, Alex; Silva Vallone, Haroldo; Pereira de Carvalho, Samuel; Dominghetti Ferreira, André (Coffee Science - ISSN 1984-3909, 2011)
This study was carried out in nematode-free land, during the period from January 04 to May 05, aimed at obtaining information on the development of coffee trees (Coffea arabica L.) grafted or non-grafted on the rootstock Apoatã IAC 2258 (Coffea canephora Pierre ex A. Froehner). The experimental design used was a randomized block with a (7 x 3) factorial split-plot arrangement and four replications, as follows: seven C. arabica cultivars and three types of seedlings (grafted, self grafted and non-grafted), evaluated in four time periods. The experiments were evaluated for plant height, plagiotropic shoots number and number of nodes on plagiotropic shoots. The results concluded that grafted seedlings were not superior to the non-grafted ones in any of the evaluated characteristics, regardless of the cultivar. But the effects of stress caused by grafting and Apoatã rootstock were observed.